Urząd generał-gubernatora w Rosji i w Królestwie Polskim - Stanisław Wiech (Czasopismo Prawno-Historyczne)
The office of general-governor was first created in Russia in 1775 and has since played an important role in the shaping of the internal policy of the Russian Empire, and, in particular, in the „Russification” process of the Polish territories. The structure of that office gave rise to a number of conflicts and animosities among various organs of central and local authorities in Russia. Despite all that, however, the power exercised by general-governor’s offices on Russian western frontiers (or, more precisely, on the eastern parts of partitioned Poland under Russian rule) were a better guarantee of a proper adjustment of the local administrative and political organs to their primary function that was effective management of regions that were ethnically, nationally, culturally, geographically, economically and religion-wise significantly different from those in the Russian Empire. Together with the social, economic and political transformations of the Russian state and the progressing liberalisation of the ‘self-governing’ system in Russia, the role and position of general-governors had gradually diminished, and their functions were successfully performed by ordinary governors. In critical situations, and at times of intensified internal conflicts, those ordinary governors were again replaced by general-governors, or specially appointed temporary or military general-governors. The once established trend, however, was on a way with no return. The institution of general-governors, characteristic of special prerogatives and rights, had prevailed the longest along the frontiers, in the regions in which the political, cultural and economic aspirations of their inhabitants did not go hand in hand with the political interests of the state and the Russian authorities. As the history of those institutions shows, the central government not only tolerated but it practically supported them in those regions, seeing them as the most effective tool through which the main objectives, i.e. unification, Russification and integration of those territories with the Empire could be achieved.